1994
DOI: 10.1139/x94-267
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of poplar leaf rust epidemics from a leaf-disk assay

Abstract: The reliability of a leaf-disk assay to assess resistance of Populusdeltoides Bartr. to Melampsoramedusae Thuëm. f.sp. deltoidae, the causal agent of poplar leaf rust, was evaluated. Leaf disks of eight host genotypes were inoculated in a spore settling tower with 11 isolates of the pathogen in all possible combinations, and the latent period, infection probability, sporulation, and progeny/parent ratio were recorded. Correlations were established between these measures and measures derived from field epidemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Similar observations were made in a previous study with M. larici‐epitea (Pei et al ., 1996). In the North American poplar rust M. occidentalis , studies showed that the results from leaf disc inoculation tests generally conformed to the extent of disease in the field (Hamelin et al ., 1994). Such evidence suggests that the leaf disc inoculation test remains an effective means of characterizing host resistance/pathogen virulence in Melampsora on poplar and willow because of its efficiency and simplicity.…”
Section: Discussionmentioning
confidence: 95%
“…Similar observations were made in a previous study with M. larici‐epitea (Pei et al ., 1996). In the North American poplar rust M. occidentalis , studies showed that the results from leaf disc inoculation tests generally conformed to the extent of disease in the field (Hamelin et al ., 1994). Such evidence suggests that the leaf disc inoculation test remains an effective means of characterizing host resistance/pathogen virulence in Melampsora on poplar and willow because of its efficiency and simplicity.…”
Section: Discussionmentioning
confidence: 95%
“…CH-11 expresses the endochitinase gene ech42 from the biocontrol fungus Trichoderma harzianum under the control of a cauliflower mosaic virus double 35S promoter, alfalfa mosaic virus leader (1). Leaf disks were used in all experiments because they were previously shown to reflect field infections (8). The fifth and sixth leaves from the index leaf were taken from at least five different trees and surface sterilized in a 1% household bleach solution for 5 min and then washed twice in sterile water.…”
Section: Methodsmentioning
confidence: 99%
“…The reliability of arti®cial inoculations of excised organs such as leaf discs have been reported in other pathosystems (HAMELIN et al 1994;FREY and PINON 1997;BE Â NAOUF and PARISI 1998;BROWN et al 1999;EVANS et al 1999;VLEESHOUWERS et al 1999). The reliability of arti®cial inoculations of excised organs such as leaf discs have been reported in other pathosystems (HAMELIN et al 1994;FREY and PINON 1997;BE Â NAOUF and PARISI 1998;BROWN et al 1999;EVANS et al 1999;VLEESHOUWERS et al 1999).…”
Section: Comparison Of the Evaluations For Twisting Rust Susceptibilimentioning
confidence: 83%
“…seedlings with few rust symptoms could be identi®ed as resistant whereas these seedlings could be the result of disease escapes. However, few studies about tree breeding improvement programmes for disease resistance have directly compared ®eld and arti®cial inoculation procedures (MILLER 1983;MARTINSSON 1987;HAMELIN et al 1994;BE Â NAOUF and PARISI 1998). elliottii) to fusiform rust (Cronartium quercuum (Berk) Miyabe ex.…”
Section: Introductionmentioning
confidence: 99%